2019
DOI: 10.9734/jammr/2019/v31i530299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Childhood Obesity among Primary School Students at Taif Governorate, Saudi Arabia

Abstract: Background: Obesity in children is rapidly emerging as a global epidemic that will have profound public health consequences as overweight children become overweight adults particularly if obesity is present in adolescence. Objectives: To determine the prevalence of overweight and obesity among school children between 6-12 years (males and females) at Taif primary schools and determine the associated dietary risk factors for overweight and obesity. Methods: A cross sectional analytic study was imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In Taif city, Saudi Arabia, childhood overweight and obesity is a public health problem affecting more than onethird of girls and almost one-fifth of boys. It confirms the significant association between some unhealthy dietary habits and increases the prevalence of childhood obesity [8]. Several studies reported that higher TV numbers of watching hours are related to increasing body mass index (BMI), decreased body fitness, and increased blood cholesterol levels [9].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In Taif city, Saudi Arabia, childhood overweight and obesity is a public health problem affecting more than onethird of girls and almost one-fifth of boys. It confirms the significant association between some unhealthy dietary habits and increases the prevalence of childhood obesity [8]. Several studies reported that higher TV numbers of watching hours are related to increasing body mass index (BMI), decreased body fitness, and increased blood cholesterol levels [9].…”
Section: Introductionsupporting
confidence: 58%
“…As regards the percentage distribution of the study children by BMI, the present study found that 15.9% of female students were overweight and obese. In Taif, KSA, in schoolboys, the prevalence of overweight and obesity were 10.7% and 7.6%, respectively; while in girls, they were 16.8% and 18.2%, respectively [8]. In Jazan, overweight and obesity were 10.1% and 12.4%, respectively, and both obesity and overweight were more frequent in children consuming more fast food [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that reading interest positively affects learning achievement (Alghamdi, 2019;Hairani & Rathni, 2017;Nugraha, 2018). However, some studies show no significant relationship between reading interest and learning achievement (Ardianto, 2020;Shihab, 2021).…”
Section: Introductionmentioning
confidence: 97%